Contemporary mathematics - Marcelino, Daisy de Borja; Remoto-Ocampo, Shrilee (Quezon City, Philippines : LORIMAR PUBLISHING INC., 2011)
This book is carefully designed to help you, pre-service teachers, to be mathematically equipped and globally competitive your skills in critical thinking, decision making, problem solving, presenting, analyzing and forecasting quantitative data.
Chapter I. Management science -- Chapter II. Probability -- Chapter III. Statistics -- Chapter IV. Shapes, similarity and measurement -- Chapter V. Exponential and logarithmic functions -- Chapter VI. Patterns, symmetry, sequence and series -- Chapter VII. Conic section and distances.
Keywords: MATHEMATICS